Clinical Outcomes of Silk Patch in Acute Tympanic Membrane Perforation - Jun Ho Lee (Clinical and Experimental Otorhinolaryngology, 2015)
ObjectivesThe silk patch is a thin transparent patch that is produced from silk fibroin. In this study, we investigated the treatment effects of the silk patch in patients with traumatic tympanic membrane perforation (TTMP).MethodsThe closure rate, otorrhea rate, and closure time in all patients and the closure time in successful patients were compared between the paper patch and silk patch groups.ResultsDemographic data (gender, site, age, traumatic duration, preoperative air-bone gap, and perforation size and location) were not significantly different between the two groups. The closure rate and otorrhea rate were not significantly different between the two groups. However, the closure time was different between the two groups (closure time of all patients, P=0.031; closure time of successful patients, P=0.037).ConclusionThe silk patch which has transparent, elastic, adhesive, and hyper-keratinizing properties results in a more efficient closure time than the paper patch in the treatment of TTMP patients. We therefore believe that the silk patch should be recommended for the treatment of acute tympanic membrane perforation.